What role for the rotating Presidency in European development policy? the case of ACP-EU relations. Issue 5 (4th July 2019) - Keijzer, Niels; Schulting, Gerard
ABSTRACT: The European Commission has the legal right of initiative to propose both legislative and non-legislative actions, including in areas where competence is shared with the member states such as development policy. This article uses the case of ACP-EU relations to show the trade-offs between the Commission's right of initiative to promote the European interest, and its own interests in the field of development policy. It presents detailed empirical observations of Commission-Presidency dynamics during the preparation of the Union's negotiating mandate for ACP-EU relations after the expiration of the Cotonou agreement in 2020. In this process, the Commission had considerable control over the calendar and on the substance of Council Working Group exchanges, while the rotating Council Presidency had comparatively little influence on the process. Developments during the first half of 2018 increased political uncertainty and raise questions marks as to the longer-term effectiveness of the Commission's post-Cotonou strategy.